Разложить ** множители1-(2x-3)^2Упростить выражение12^2 - (x-7)^2 -(5-x)*(19+x)

0 голосов
49 просмотров

Разложить на множители
1-(2x-3)^2
Упростить выражение
12^2 - (x-7)^2 -(5-x)*(19+x)


Алгебра (36 баллов) | 49 просмотров
0

во втором точно верная запись?

0

Да

Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

1^{2}-(2x-3)^{2}=(1-2x+3)(1+2x-3)=(4-2x)(2x-2) \\ 12^{2}-(x-7)^{2}-(5-x)(19+x)= \\ =(12-x+7)(12+x-7)-(5-x)(19+x)= \\ =(19-x)(5+x)-(5-x)(19+x)=
\\ =95-5x+19x-x^{2}-95+19x+5x+x^{2}=38x
(63.8k баллов)